2022
DOI: 10.1039/d2ea00068g
|View full text |Cite
|
Sign up to set email alerts
|

Furoyl peroxynitrate (fur-PAN), a product of VOC–NOxphotochemistry from biomass burning emissions: photochemical synthesis, calibration, chemical characterization, and first atmospheric observations

Abstract: The recent increase in frequency and severity of wildfires (WF) in the western U.S. has renewed interest in understanding the impact of WF emissions on their chemistry in the atmosphere....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Nitrate and PAN type compounds are potential wildfire/biomass burning degradation products, although field observations and laboratory studies are extremely limited. Furoyl peroxynitrate (C 4 H 3 O−C(O)−OONO 2 ), formed following the atmospheric degradation of 2-furfural, 165 is the only furanoid nitrate to be reported in wildfire plumes to date. UV spectra or photolysis product studies of furanoid nitrates are currently not available, but it is expected that initial photolysis occurs at the O−NO 2 bond.…”
Section: Benzofurans + Hν: 23-dihydrobenzofuran 23-benzofuran 2-methy...mentioning
confidence: 99%
See 4 more Smart Citations
“…Nitrate and PAN type compounds are potential wildfire/biomass burning degradation products, although field observations and laboratory studies are extremely limited. Furoyl peroxynitrate (C 4 H 3 O−C(O)−OONO 2 ), formed following the atmospheric degradation of 2-furfural, 165 is the only furanoid nitrate to be reported in wildfire plumes to date. UV spectra or photolysis product studies of furanoid nitrates are currently not available, but it is expected that initial photolysis occurs at the O−NO 2 bond.…”
Section: Benzofurans + Hν: 23-dihydrobenzofuran 23-benzofuran 2-methy...mentioning
confidence: 99%
“…The authors observed IR bands associated with the presence of −ONO 2 and −OONO 2 groups, suggesting the formation of organic nitrates. It is likely that these products include furoyl peroxynitrate (fur-PAN), which has been observed in aged biomass burning plumes and whose properties have been studied by Roberts et al 165 Other furanaldehydes, including 3-furfural and 5-methyl-2-furfural, are also likely to form peroxynitrates, though no studies have experimentally evaluated the product yields of these potential NO x reservoirs.…”
Section: Acs Earth and Spacementioning
confidence: 99%
See 3 more Smart Citations